Soziale Umweltrisikofaktoren und psychische Erkrankungen: Einblicke in zugrunde liegende Gehirnmechanismen am Beispiel der Urbanizität = Social environmental risk factors and mental disorders - Haller, Leila; Meyer-Lindenberg, Andreas (Der Nervenarzt, 2012)
Summary: The importance of social environmental factors for mental disorders is well known; nonetheless explanations of the underlying associations are still incomplete. For example this holds true for the schizophrenia risk factor urban upbringing (early urbanicity), which puzzled researchers for a long time. This article reports on recently identified neural correlates of this factor in the context of social stress processing. Drawing on this example, it is demonstrated how the identification of such correlates can contribute to the etiological understanding of mental disorders. While including genetic risk mechanisms and gene-environment interactions, a theoretical model is specified that postulates changes in the perigenual anterior cingulate cortex (pACC) and a heightened sensitivity towards social stressors as the relevant link between risk of schizophrenia and early urbanicity.